2016
DOI: 10.2196/publichealth.5184
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Web and Telephone Responses From a National HIV and AIDS Survey

Abstract: BackgroundResponse differences to survey questions are known to exist for different modes of questionnaire completion. Previous research has shown that response differences by mode are larger for sensitive and complicated questions. However, it is unknown what effect completion mode may have on HIV and AIDS survey research, which addresses particularly sensitive and stigmatized health issues.ObjectivesWe seek to compare responses between self-selected Web and telephone respondents in terms of social desirabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Besides the design of the items, their content could also influence item nonresponse [26]. For instance, items asking about sensitive subjects could have higher nonresponse than items with nonsensitive content [34]. However, we did not perceive this behavior in our study.…”
Section: Discussionmentioning
confidence: 84%
“…Besides the design of the items, their content could also influence item nonresponse [26]. For instance, items asking about sensitive subjects could have higher nonresponse than items with nonsensitive content [34]. However, we did not perceive this behavior in our study.…”
Section: Discussionmentioning
confidence: 84%
“…For instance, some respondents could over‐report positive behaviors like mask‐wearing even if they typically do not wear a mask in public and under‐report negative behaviors like not washing their hands to appear to be following public health guidelines. Notably, however, research does suggest that social desirability bias for self‐reported health behaviors is typically lower in online surveys like ours 39 . Relatedly, in asking individuals to reflect on the past month, individuals could simply forget whether they engaged in each activity, potentially leading to some degree of error in each of our measures.…”
Section: Limitationsmentioning
confidence: 81%
“…These findings do not seem to be driven entirely by privacy concerns; if these concerns were paramount, we would expect the greatest number of women to endorse MST on the DRRI. There is some evidence that interviews can produce higher estimates of certain behaviors because interviewers can clarify questions and motivate participants (e.g., Jones et al, 2016); this factor may explain why female participants endorsed MST most frequently on the study interview.…”
Section: Discussionmentioning
confidence: 99%